Advances in affective and pleasurable design - Ji, Yong Gu (Boca Raton, Florida : CRC Press, 2013)
This book focuses on a positive emotional approach in product, service, and system design and emphasizes aesthetics and enjoyment in user experience. This book provides dissemination and exchange of scientific information on the theoretical and practical areas of affective and pleasurable design for research experts and industry practitioners from multidisciplinary backgrounds, including industrial designers, emotion designer, ethnographers, human-computer interaction researchers, human factors engineers, interaction designers, mobile product designers, and vehicle system designers. This book is organized in nine sections which focus on the following subjects: I: Designing for Diversity II: Cultural and Traditional Aspects III: Ergonomics and Human Factors IV: Product, Service, and System Design V: Human Interface in Product Design VI: Emotion and UX Design VII: Design and Development Methodology VIII: Diverse Approaches: Biosignals, Textiles, and Clothing IX: Novel Devices, Information Visualization, and Augmented Reality Sections I through III of this book cover special approaches in affective and pleasurable design with emphasis on diversity, cultural and traditional contexts, and ergonomics and human factors. Sections IV through VII focus on design issues in product, service, and system development, human interface, emotional aspect in UX, and methodological issues in design and development. Sections VIII and IX handle emotional design approaches in diverse areas, i.e. biosignals, textiles, and clothing, and emerging technologies for human interaction in smart computing era. Overall structure of this book is organized to move from special interests in design, design and development issues, to novel approaches for emotional design.
Section 1. Designing for diversity -- section 2. Cultural and traditional aspects -- section 3. Ergonomics and human factors -- section 4. Product, service, and system design -- section 5. Human interface in product design -- section 6. Emotion and UX design -- section 7. Design and development methodology -- section 8. Diverse approaches : biosignals, textiles, and clothing -- section 9. Novel devices, information visualization, and augmented reality.
Includes index.
Keywords: PRODUCTION DESIGN